Analisis Semiotik Pesan Dakwah Lirik Lagu Nasyid “Pandangan Mata” Karya Hijjaz (Model Charles Sanders Peirce) - Ridho, Ali (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
The road to preaching has a variety of ways, especially the media used. Among them is through the type of Nasyid religious music media. Among the Nasyid groups whose songs contain calls for Islamic da'wah are the Nasyid Hijjaz Group with the song